The role of corn waste product innovation toward the economic growth of society (Case study on MSMEs in Ketawang Village) - Aliya, Unsa Farrichatun; Atsil, Irfana; Rachmawati, Dwi (MEC-J (Management and Economics Journal), 2017)
The Role of Corn Waste Product Innovation toward The Economic Growth of Society, this research aims to find out the influence of the corn waste product innovation that usually does not have the value of sales in the market share of the economic growth of society, this research using mixed methods to test the hypothesis with quantitative methods as a support from qualitative methods used by the researchers. The results from the qualitative research that innovation is indeed affected the economic growth of society revealed by the results of the interview an expert trusted and accurate and the results of quantitative research stated that innovation variables (X) have a positive effect on economic growth (Y), with total influence of 91.1 % positive influence, this means of increasing innovation and will affect the improvement of The economy.Key Words: Innovation, Economic growth, Mixed Method, MSMEs, Corn Husk Waste